Feminist Translation of Six Records of a Floating Life - Aiqing Wang (İstanbul Üniversitesi Çeviribilim Dergisi)
浮生六记 Fusheng Liuji ‘Six Records of a Floating Life’ is an autobiography and the chef-d’oeuvre of 沈复 Shen Fu (1763-1825), which concerns delightful trivialities in his impoverished life and his wife 芸 Yun, a meritorious woman characterised by intelligence, diligence and punctiliousness. As an illustrious 性灵 xingling work enriched by literary, aesthetic and linguistic prowess, Six Records of a Floating Life has been rendered into English by an illustrious bilingual writer and translator 林语堂 Lin Yutang (1895-1976) and Shirley M. Black, as well as Leonard Pratt and Su-hui Chiang, whose version is featured by a socio-historical perspective (Lu 2010). In this research, I scrutinise Pratt and Chiang’s translation under the framework of feminist translation (Flotow 1991), exploring strategies of supplementing, hijacking as well as prefacing and footnoting. In the introduction section, Pratt and Chiang extol the heroine Yun and introduce women serving as courtesans in Qing (1644-1912) China. Additionally, the translators also employ annotations to justify Yun’s provocative utterances. Apart from prefacing and footnoting, Pratt and Chiang also deploy strategies of supplementing and hijacking, so as to highlight Yun’s merit and avoid dated expressions.